COVID-19 infection during pregnancy - maternal and perinatal outcomes: a tertiary care centre study - Hassan, Nazia; Muzamil, Mudasir; Banday, Dawood (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: With the exponential increase in the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2/COVID-19) worldwide, an increasing proportion of pregnant women are now infected during their pregnancy. The knowledge gained from previous human coronavirus outbreaks suggests that pregnant women and their fetuses are particularly susceptible to poor outcomes. The aim of this study was to summarize the maternal and perinatal outcomes of pregnant women infected with COVID-19 during their pregnancy. Methods: Eligibility criteria included pregnant women positive for COVID-19 as detected by real-time polymerase chain reaction (PCR) or dual fluorescence PCR-confirmed SARS-CoV-2 infection. Results: A total of 38 pregnant women positive for COVID-19 as confirmed by RT-PCR, were included in the study. 21% cases had preterm deliveries and LSCS was the preferred mode of delivery in 23 of 38 i.e., 60.5% cases. There was a tendency for low Apgar score at birth, higher rates of fetal distress, meconium, NICU admissions. There was one IUD and one neonatal death. The treatment patterns of COVID-19 infection among pregnant women during their pregnancy or following delivery was mostly supportive in the form of oxygen and antibiotic therapy. Conclusions: Although the majority of mothers were discharged without any major complications, severe maternal morbidity as a result of COVID-19 and perinatal deaths were reported. Vertical transmission of the COVID-19 could not be ruled out. Pregnant infected women had different symptoms, and they were given mostly supportive treatments than the general infected population. Careful monitoring of pregnancies with COVID-19 and measures to prevent neonatal infection are warranted.